(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The last decade has been accompanied by the emergence of a large number of studies on the role of small, non-coding RNA molecules (micro-RNAs). The study of miRNAs is important not only for a fundamental understanding of the mechanisms of intracellular regulation, but also has a high practical value as non-invasive biomarkers for early diagnosis of liver fibrosis. Current research provides new potential approaches to the therapy of liver fibrosis.